Being A Chronic Patient in The Process of Probation; A Case Report - Gülmez, Özge; Akcan, Ramazan; Tümer, Ali Rıza (The Bulletin of Legal Medicine, 2021)
Probation is a key component contemporary penal systems and socio-pedagogical sanction. Probation implementation aims re-adaptation of convict to society without breaking his or her social environment during determined probation period.While healthy peeople fullfile these tasks smoothly, convicts with chronic illnes might unable to fullfile these tasks because of their health problems. For detection of this stiuation a report, assessing the clinical state of convict, is requested from forensic experts. In thıs context, there might be malingering convicts that need to be examined in detail for a differential diagnosis. In order to draw attention and increase the awareness of physicians to similar cases; this paper aims to report a patient trasferred to forensic medicine clinic because of suspicion of malingering by probation directorate for evaluation the ability of working in cleaning , repair or landsacping works in a public institution four hours/day.
Keywords: Probation; Chronic Disease; Forensic Medicine